Attitude and Perception of the General Public about Rain Harvesting: Financial Implications for Cape Coast Metropolis in Ghana (International Journal of Technology and Management Research, 2020)
The continuous destructions to water bodies while the demand for potable water increases; call for immediate move to seek and improve the adoption of alternative water sources to augment the existing sources. Though Ghana has a rain harvesting strategy, very little seems to be done to improve its implementation and to sensitize the public on its adoption. It is an established fact that adoption is premised on perception but very little has been done to uncover the perception of the general public on rain-harvesting and the portability of rain water as alternative water source. This study seeks to resurrect the need to look in the direction of rain harvesting. Mixed method strategy was adopted to address the stated objectives. The results indicate that greater number of the respondents did not consider untreated rainwater as good enough for drinking but fit for all other domestic uses. The respondents identified lack of appropriate and affordable rain-harvesting system, mode of storage, contaminations with microbes when stored for long and softness as the demoralizing factors that inhibit rainwater harvesting. In conclusion, the analyses showed that rainwater harvesting is on the lower side in the area of adoption among households and major consumers of water in Cape Coast. The results confirm the 2010 census that rain harvesting is not a major source of water to the people of Cape Coast metropolis. The study recommends that stakeholders such as the Ministry of Sanitation and Water Resources must embark on mass education on the need to adopt rainwater as complement to traditional source of water and also support experts to design comprehensive rain-harvesting technique which will improve collections, storage and distribution at an affordable rate for the general public and effectively publicise it for adopts and use. Citation: Abena Yeboah Abraham1, Prince Adjei2 and Doris Ohene Ntim3. Attitude and Perception of the General Public about Rain Harvesting: Financial Implications for Cape Coast Metropolis in Ghana, 2020; 5(1): 30-44. Received: (February 6, 2020) Accepted :( (March 31, 2020)
Keywords: Rain Harvesting; Perception; Adoption; Flood, Financial; Metropolis